Effects of the Pesantren Law on Indonesia's Education System – A Projection - Nadia Fairuza Azzahra (Center for Indonesian Policy Studies (CIPS), 2020)
Pesentrens, or Islamic Boarding Schools, plays a significant role in offering parents wider options for education in Indonesia. In addition to offering education according to religious traditions, they also provide more affordable and accessible education for low-income families in rural areas. In September 2019, the Indonesian House of Representatives passed the "Pesantren Law". The law offers to provide states funds and aims to standardize the educational quality of pesantrens, with the aim of raising quality. However, the law raises several questions, including the possible erosion in the diversity of the types of pesantrens available. Read our discussion paper to be part of the conversation on how the recent Pesantren Law could impact pesantrens throughout the country. Screen reader support enabled.
Keywords: 330